PERIODICITY OF DECISIONS OF SYSTEM OF TWO NONLINEAR DIFFERENTIAL EQUALIZATIONS OF THE THIRD ORDER - Краснодембський, Адам Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The terms of meeting of sequences, which determine the upshots with the periodic components of some system of two nonlinear differential equalizations of the third order are set in the article.